Civilized Oppression - Harvey, J. (Rowman & Littlefield Publishers, 1999)
In this important new work, J. Harvey analyzes what is involved in serious but subtle forms of oppression involving neither physical violence nor the use of law, and argues for the crucial role of morally distorted relationships in such oppression. She uncovers a set of underlying moral principles that account for the immorality of civilized oppression, and points to some of the implications for social and institutional life.